Exploring Sustainable Practices in E-Commerce: Unlocking Competitive Advantage for Modern Enterprises in the Evolving Digital Era - Mukhammadkhon, Sattikulov; Ciptagustia, Annisa (Eastasouth Institute, 2025)
In the digital economy, sustainability has become a strategic driver of customer loyalty and competitive differentiation in e-commerce. This study investigates how environmentally responsible and ethically sound practices—such as eco-friendly packaging, carbon-neutral shipping, and ethical sourcing—enhance brand trust, customer retention, and long-term profitability. Using a systematic literature review and case study analysis, the research explores the connection between sustainability efforts and key business outcomes. Findings indicate that while sustainable practices may incur short-term costs, they contribute to improved brand reputation, reduced supply chain risks, and stronger alignment with environmentally conscious consumers. Ethical sourcing enhances transparency and reduces reputational risks, while green logistics minimize environmental impact. The study emphasizes the need for e-commerce businesses to embed sustainability within operational strategy to meet evolving consumer expectations and market demands. Despite the reliance on secondary data, the insights offer actionable guidance for companies seeking to balance ethical responsibility with commercial success.